Analysis of Seismic Sloshing Displacements in Rectangular Liquid Storage Tanks with SPH Method - Güray, Ersan; Aksel, Murat; YAZICI, GÖKHAN (My University, 2018)
In this study, Smoothed Particle Hydrodynamics (SPH) method was used to model sloshing response of a rectangular tank subjected to horizontal earthquake base excitation. An experiment and a numerical study with ANSYS Fluent flow modeling software are performed to verify the outputs of the SPH model. The sloshing displacement profiles obtained from the SPH model closely matched the free surface displacements obtained from the experiment and the flow modeling software. The SPH model described in this study was highly efficient at capturing discontinuities and working with moving boundaries without having to re-mesh the model at each time step.

Bu çalışmada, yatay yönde yer sarsıntısına maruz kalan prizmatik bir tankta gerçekleşen çalkalanma modellemesi düzgünleştirilmiş parçacık hidrodinamiği yöntemiyle (SPH) gerçekleştirilmiştir. SPH yöntemi sonuçları bir deney ve ANSYS Fluent modeli sonuçlarıyla doğrulanmıştır. Deneyden ve Fluent modeliyle elde edilen çalkalanma profilleri burada ele alınan SPH yöntemi sonucuyla müthiş bir uyumluluk göstermektedir. Bu çalışma irdelenen SPH yöntemi, süreksizlikleri yakalama ve hareketli sınırları ele almada oldukça etkilidir.
Prizmatik Sıvı Tanklarında oluşan Sismik Çalkalanmaların SPH Yöntemiyle İncelenmesi
Keywords: Deprem; Çalkalanma; Sıvı Tankları; Earthquake; Sloshing; Liquid Storage Tanks; SPH